PERENCANAAN PENGEMBANGAN KAWASAN WISATA BANYUURIP DESA JATIMULYO, KECAMATAN DLINGGO, KABUPATEN BANTUL - Eka Widyaningsih (UNHI Press, 2020)
Two objectives of this study are the development of tourism potentials and the environmental conservation in Banyuurip tourism area, Jatimulyo Village, Dlinggo District, Bantul Regency, Special region of Yogyakarta. Our goal is to improve the physical quality of the site for competitive capacity. The issue concerning comprehensive spatial planning, tourist attractions, and optimization of human resources should be address more seriously. The spatial planning development concept applies in Banyuurip area should covered 4 planning approaches (4A) : Attraction, Accessibility, Amenity, and Ancillary.